Rancang Bangun Alat Pencacah Sayuran Dengan Variasi 3 Jenis Mata Pisau Berkapasitas 1 Kg/Menit Untuk Pakan Unggas - Pego Alminson; Erizal Erizal; Een Tonadi (LPPM Politeknik Jambi, 2025)
The livestock sector plays a significant role in providing quality feed to support the growth and productivity of poultry. Vegetables are widely used as an alternative feed, but the chopping process is still often done manually, which is time-consuming, labor-intensive, and produces uneven cuts. This study aims to design and build a vegetable chopper equipped with three types of blades and a chopping capacity of 1 kg per minute. The research method includes literature studies, conceptual design, manufacturing process, and testing of the chopped results. The machine consists of a 2.2 kW electric motor with 2850 RPM, an 8 cm long shaft, and three types of blades. The test results show that using three blades produces the most uniform chopped results, meeting the poultry feed standards (50–100 mm). This tool is expected to assist small and medium-scale farmers in preparing poultry feed more efficiently and hygienically.